2018
DOI: 10.1016/j.polymertesting.2017.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparing damage from low-velocity impact and quasi-static indentation in automotive carbon/epoxy and glass/polyamide-6 laminates

Abstract: The results of a low-velocity impact programme on both carbon/epoxy and glass/polyamide-6 composite laminates are compared to the results of quasi-static indentation. Cross-ply and quasiisotropic stacking sequences are impacted and quasi-static indentation tests are performed up to the same maximum displacement. The response of the laminates to both test methods is compared in terms of force-displacement behaviour, dissipated energy and resulting damage. Significant differences between low-velocity impact and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Nettles and Douglas [11] and Lee and Zahuta [13] also state that these two tests induce similar failure mechanism, with very similar damages and force × displacement curves, for carbon/epoxy composites. On the contrary, Lawrence et al [14] and Spronk et al [15] reported different damages and curves from QSI and drop-weight tests for glass-S2/epoxy, carbon/epoxy and glass/polyamide composites.…”
Section: Resultsmentioning
confidence: 96%
“…Nettles and Douglas [11] and Lee and Zahuta [13] also state that these two tests induce similar failure mechanism, with very similar damages and force × displacement curves, for carbon/epoxy composites. On the contrary, Lawrence et al [14] and Spronk et al [15] reported different damages and curves from QSI and drop-weight tests for glass-S2/epoxy, carbon/epoxy and glass/polyamide composites.…”
Section: Resultsmentioning
confidence: 96%
“…Both samples are shown in Figure 2 together with the corresponding C-scan amplitude and time-of-flight (TOF) images, showing the complex damage distribution at the impact location. The C-scan results are obtained in reflection mode using dynamic time gating [26]. A focused transducer at 5 MHz (H5M, General Electric) is employed.…”
Section: Methodsmentioning
confidence: 99%
“…The impact event was done with a fully instrumented in-house developed drop tower with anti-rebound system (to prevent double hits), a 7.72 kg impactor with 16 mm impactor-tip was mounted. The measured impact energy was 6.3 J, resulting in barely visible impact damage for this type of composite [1]. In the remainder of the text, this sample is indicated with CFRPBVID (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…A major drawback of composites is their sensitivity to internal damage features. Especially for carbon fiber reinforced plastics (CFRP) laminates, a small impact event could lead to large internal delaminations affecting the structural integrity [1]. To assure the structural performance of composite components, several non-destructive testing (NDT) techniques have been developed and implemented over the last decades [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%